ULTRASONIC AND DOPLEROMETRIC CHARACTERISTICS OF SMALL PELVIS ORGANS OF POSTMENOPAUSAL WOMEN WITH PHYSIOLOGICAL COURSE AND WITH INTRAUTERINE FLUID - Aliona Momot; Anna Kuzmina; Tetiana Kovaliuk; Natalia Lukianenko (Bogomolets National Medical University, 2019)
The article presents the peculiarities of ultrasound and Doppler measurements of the pelvic organs of postmenopausal women with physiological course and in the presence of intrauterine fluid. The main purpose of the study was to investigate the features of ultrasound and Doppler examination of the pelvic organs of postmenopausal women with physiological course and in the presence of intrauterine fluid. The relevance of the study of this pathology is that during menopause, the number of women with diseases of the female reproductive system increases. Therefore, the study of age-specific features of the internal genital organs is of fundamental importance for the diagnosis of the initial manifestations of various pathological conditions in the postmenopausal period. The methodology of the study consisted of a prospective study of 130 postmenopausal women with intrauterine fluid and postmenopausal women with physiological course. Following a general clinical examination of patients in both groups, a comprehensive ultrasound study was performed, which included gray-scale ultrasound and Doppler imaging to assess vascular imaging. The article presents the result of the study and found that postmenopausal women with a physiological course revealed that the qualitative and quantitative parameters of blood flow in the uterine arteries change over the duration of the postmenopausal period. This process was characterized by a decrease in both Vmax and Vmin. The value of the peripheral resistance indices, especially IR, remained quite stable, indicating a decrease in the level of perfusion. With the progress of menopause, there is a gradual sclerosis of the vessels, which is determined by the gradual decrease in the indices of vascular resistance, in vessels as far from the main vessels that supply the uterus, to vessels of smaller diameter. In contrast, postmenopausal women with intrauterine fluid had decreased peripheral resistance, indicating an increase in circulatory intensity in the uterine bloodstream and an increase in perfusion. The results of the study indicate that postmenopausal women with intrauterine fluid have characteristic features when conducting ultrasound and doppler measurements of pelvic organs compared with postmenopausal women with physiological menopausal course. Thus, for postmenopausal women with a physiological course of menopause with an increase in the duration of menopause, there is a gradual sclerosis of the vessels, which is determined by the gradual decrease in the indicators of vascular resistance, in vessels as distant from the main vessels that feed the body of the uterus to the body of the uterus. In postmenopausal women with intrauterine fluid, and especially with an increase in its number, changes occur in the uterine vessels, as evidenced by changes in the Doppler measurement of peripheral resistance, indicating an increase in blood circulation in the uterine blood vessels, and an increase in perfusion as a result of decrease of peripheral resistance.